Morphological characteristics and motor skills of young students with different levels of engagement in physical activities (Características morfológicas y habilidades motrices de estudiantes jóvenes con diferentes niveles de participación en actividad - Batez, Maja; Krsmanović, Branko; Mikalački, Milena; Čokorilo, Nebojša; Simić, Marijana; Ruiz-Montero, Pedro Jesús (Retos, 2018)
The overall orientation of the research problem is focused on the physical activity level of the participants from the aspect of different intensities of motor engagement and their impact on morphological characteristics and motor skills with an intention of determining whether there are statistically significant differences between groups. In a sample of 103 students, aged between 18 and 20 years (18.9 ± 0.4), the female students were divided into three subsamples according to the level of physical activity: highly active, active and inactive. The study which was conducted had a transversal character. The data obtained in the survey were analysed using the univariate (ANOVA) and multivariate (MANOVA) statistical methods. The motor skills mere monitored by the use of the Eurofit Test Battery (wide-angle seated forward bend, standing long jump, pull-up endurance, 10 x 5m shuttle run and endurance shuttle run- beep test). The following morphological characteristics were considered: height, weight, body mass index, percentage of muscular mass and fat mass, as well as waist circumference. The obtained results indicate the existence of statistically significant differences between the % body muscle mass´ groups (p < 0.05) and motor skills parameters (sit and reach, p<0.01; standing broad jump, bent arm hang, 10x5m shuttlerun, beep test, p<0.001) of participants according to physical activity level. In conclusion, participants with a high level of physical activities have higher average values than the participants with light level of physical activities when considering the variables for assessing pliability, strength and agility. Resumen. La orientación general del problema de investigación se centra en el nivel de actividad física de las participantes desde el aspecto de diferentes intensidades de compromiso motor y su impacto en las características morfológicas y habilidades motrices con la intención de determinar si existen diferencias estadísticamente significativas entre los grupos. En una muestra de 103 alumnas, con edades comprendidas entre los 18 y 20 años (18,9 ± 0,4), las estudiantes fueron divididas en tres grupos de acuerdo con el nivel de actividad física de cada uno: muy activas, activas e inactivas. El estudio llevado a cabo tuvo un carácter transversal. Los datos obtenidos mediante cuestionarios fueron analizados utilizando un análisis de la varianza (ANOVA) y un análisis multivariante de la varianza (MANOVA). Las habilidades fueron controladas mediante la batería Eurofit y para las características morfológicas, se midió la altura, peso, índice de masa corporal, porcentaje de masa muscular, masa grasa y la circunferencia de la cintura. Los resultados obtenidos indican la existencia de diferencias entre los grupos estudiados respecto al % de masa muscular (p <0.05) y las habilidades motrices (flexibilidad-inclinación hacia adelante, p<0.01; salto de longitud a pie, fuerza resistencia mediante flexión de brazos, 10 x 5 m carrera de ida y vuelta y Beep Test, p<0.001) de los participantes según el nivel de actividad física. En conclusión, las participantes con alto nivel de actividad física tienen mayores valores de habilidad motriz que las participantes que el resto en función de las variables flexibilidad, capacidad aeróbica, fuerza y agilidad.